Flap Thickness Measurement Using the Amadeus Microkeratome - Ali M. El Ghatit,; Adnan H. Marzouki, (Journal of King Abdulaziz University: Medical Sciences, 2023)
To evaluate the predictability of flap thickness measurement with the 160 micron head of the Amadeus microkeratome and its complications. A retrospective study of 100 eyes underwent LASIK where the flap was created with the 160 microns head of the Amadeus microkeratome. The flap measurement was done by applying the ultrasonic pachymeter on the center of the cornea before and after the cut, the difference was considered the flap thickness. The mean flap thickness for the right eye was 167 ± 6 for the right eye, 154 ± 19 for the left eye. The flap thickness had a highly significant positive correlation (Pearson correlation) with the corneal thickness while no correlation was found with the spherical equivalent, keratometer readings and flap diameter. The second cut was found to be thinner than the first cut. The 160 microns head usually give within the range of this reading, but not less. The second cut is usually thinner. This data will help the user of the microkeratome to estimate the residual bed thickness to avoid post LASIK ablation complications.